Intensi Masyarakat terhadap Pariwisata Berkelanjutan - Nugroho, Redo; Suwaryono, Ixora Lundia (SAFE-Network, 2024)
This article aims to identify factors that influence tourists' intention to visit sustainable tourism destinations in Penglipuran Tourism Village. This research uses the theory of planned behavior which is expanded by adding moral reflectiveness variables. The research method used is quantitative with a purposive sampling technique, where data were collected through questionnaires distributed via Google Forms to 144 respondents. Data analysis was conducted with partial least squares structural equation modeling (PLS-SEM) using SmartPLS 3.0. The results showed that subjective norm, perceived behaviour control, and moral reflectiveness variables positively influence the intention to visit sustainable tourism in Penglipuran Village. In contrast, the attitude variable does not affect the intention to visit sustainable tourism in Penglipuran Tourism Village. The implication of this research is expected to provide information for tourism managers and the government to increase visits to Penglipuran Tourism Village through promotion through influencers, improving facilities, and education about sustainable tourism.